Detection of human sarcocystosis using dried blood on filter papers: An immunofluorescent antibody test - Sharudin, P.S.; Rahimi, Razuin; Latif, Baha; Kutty, Methil Kannan; Muslim, Azdayanti; Abdul Rahim, A.S.; Abdul Aziz, M.; Mahfudz, Anis Shafina; Lim, Yvonne Ai Lian; Heo, Chong Chin; Md Noor, Shahidan; Hiu, J.; et al. (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Sarcocystosis, a parasitic infection caused by a protozoa belonging to the genus Sarcocystis, is found worldwide in both and animals. Sarcocystis spp., require two animal hosts to complete their life cycle. The infection has gathered more global attention after recent outbreaks, especially amongst wester travellers to Malaysia. Other than sporadic cases and the current outbreaks, little information is available regarding human Sarcocystis infection in Malaysia. The present study aims to determine the prevalence of sarcocystosis among humans using an immunofluorescent antibody (IFA) test applied to dried blood on filter papers. A total of 200 blood samples were collected on filter papers from autopsy cases at two Malaysian hospitals: Sungai Buloh Hospital (peninsular Malaysia) and Queen Elizabeth Hospital (Malaysian Borneo). Antigens were prepared from bradyzoites harvested from positive goats’ muscle samples. Of the 200 samples, 32 (16%) had Sarcocystis antibodies that showed positive fluorescence reactions on filter papers. There was no significant difference (t-test, p value > 0.05) in prevalence rates between samples collected from autopsies at peninsular Malaysia and Malaysian Borneo. The results demonstrated that the filter paper technique can be used as one of the alternative serological tests in the diagnostic of human sarcocystosis. © 2019, Malaysian Society for Parasitology. All rights reserved.